An isogeometric analysis Bézier interface element for mechanical and poromechanical fracture problems. (17th December 2013) - Irzal, F.; Remmers, J.J.C.; Verhoosel, C.V.; de, R.
SUMMARY Interface elements are a powerful tool for modelling discontinuities. Herein, we develop an interface element that is based on the isogeometric analysis concept. Through Bézier extraction, the novel interface element can be casted in the same format as conventional interface elements. Consequently, the isogeometric interface element can be implemented in a straightforward manner in an existing finite element software by a mere redefinition of the shape functions. The interface elements share the advantages of isogeometric continuum elements in that they can exactly model the geometry. On the other hand, they inherit the simplicity of conventional interface elements, but also some deficiencies, such as the occurrence of traction oscillations when a high interface stiffness is used. The extension towards poroelasticity is rather straightforward, and in this situation, the smoother flow profiles and the ensuing preservation of local mass balance are additional advantages. These are demonstrated at the hand of some example problems. Copyright © 2013 John Wiley & Sons, Ltd.